2013
DOI: 10.1016/j.jconrel.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes coated with thiolated chitosan enhance oral peptide delivery to rats

Abstract: The aim of the present study was the in vivo evaluation of thiomer-coated liposomes for an oral application of peptides. For this purpose, salmon calcitonin was chosen as a model drug and encapsulated within liposomes. Subsequently, the drug loaded liposomes were coated with either chitosan–thioglycolic acid (CS–TGA) or an S-protected version of the same polymer (CS–TGA–MNA), leading to an increase in the particle size of about 500 nm and an increase in the zeta potential from approximately − 40 mV to a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 33 publications
1
58
0
Order By: Relevance
“…[22][23][24][25][26][27][28] Furthermore, the liposomes can improve the oral bioavailability of drugs poorly absorbed through the gastrointestinal tract and alter the in vivo distribution of the drugs encapsulated into liposomes, to increase the therapeutic index. 22,[29][30][31][32] Currently, liposomes have been considered one of the most promising drug delivery carriers. Several preparation technologies for liposome development have been studied in recent years, including the film hydration method, ethanol injection method, and high-pressure homogenization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28] Furthermore, the liposomes can improve the oral bioavailability of drugs poorly absorbed through the gastrointestinal tract and alter the in vivo distribution of the drugs encapsulated into liposomes, to increase the therapeutic index. 22,[29][30][31][32] Currently, liposomes have been considered one of the most promising drug delivery carriers. Several preparation technologies for liposome development have been studied in recent years, including the film hydration method, ethanol injection method, and high-pressure homogenization.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Thus, a number of studies showed the liposome carrier could improve the oral bioavailability of poorly bioavailable drugs and change the in vivo distribution of entrapped drugs. [29][30][31][32] For example, Wang et al developed long-circulating nanoliposomes of quercetin, prepared by the emulsified evaporation-low temperature solidification method, using glyceryl behenate and Tween ® 80 as carriers. The researchers showed that the oral absorption of the longcirculating quercetin liposomes in the liposomal formulation, in mice, was better than that of quercetin suspension.…”
Section: Introductionmentioning
confidence: 99%
“…General theories of the molecular basis of adhesion have been applied to the discussion of mucoadhesion [31]. Chitosan performs well as a mucoadhesive dosage form both in vivo [32][33][34][35][36][37][38] and in vitro [2,25,26,28,[39][40][41][42][43][44][45][46] and it is therefore of interest to determine the strength of the basic interactions related to this important property.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was possible to synthesise very small, coated liposomes around 37 nm in size. In some previous studies, thiolated chitosan coated liposomes synthesised for the use in oral peptide delivery were in the size range of 600 -700 nm (Gradauer et al, 2013). In another study where chitosan coated liposomes were used to encapsulate leuprolide, the sizes were…”
Section: Size and Zeta Potential Distribution Datamentioning
confidence: 99%